2012
DOI: 10.1086/666630
|View full text |Cite
|
Sign up to set email alerts
|

Chinks in the Armor: Activation Patterns of Hollow-Bore Safety-Engineered Sharp Devices

Abstract: A retrospective review of secondary injury data was used to evaluate the characteristics of percutaneous injuries from safety-engineered sharp devices. Injury rates and safety device activation rates differed by healthcare provider type. Approximately 22.8%-32% of injuries could have been prevented had an available safety feature been activated after use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…21 Though there is a general agreement on reduction of SIs after routine use of SEDs, a few controversies exist. 22,23 It is also postulated that reporting of SIs during the use of SED would be more rigorous, because the occurrence was against the healthcare worker's expectation. Therefore, there may be a bias in reporting higher SIs when SEDs are used.…”
Section: Discussionmentioning
confidence: 99%
“…21 Though there is a general agreement on reduction of SIs after routine use of SEDs, a few controversies exist. 22,23 It is also postulated that reporting of SIs during the use of SED would be more rigorous, because the occurrence was against the healthcare worker's expectation. Therefore, there may be a bias in reporting higher SIs when SEDs are used.…”
Section: Discussionmentioning
confidence: 99%
“…4 Sharps injuries significantly decrease with the use of safety-engineered sharps devices (SED). 5 However, with increasing use of SED, the proportion of SI sustained from SED (over non-SED) increases 6 and the majority of 'after-use' SI are due to non-or incomplete activation of SED. 6 From an early time, the activation of SED has been recognised as a key component in SED efficacy, and monitoring of activation rates is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, with increasing use of SED, the proportion of SI sustained from SED (over non-SED) increases 6 and the majority of 'after-use' SI are due to non-or incomplete activation of SED. 6 From an early time, the activation of SED has been recognised as a key component in SED efficacy, and monitoring of activation rates is recommended. 7 Monitoring of SED activation rates can only effectively be achieved by decanting SC contents and counting activated and non-activated devices under controlled environments.…”
Section: Introductionmentioning
confidence: 99%
“…5 Nevertheless, needlestick injuries still occur, even after training with devices containing safetyengineered protection mechanisms. [6][7][8][9][10][11] Current regulations include detailed specifications for safety-engineered protection mechanisms, such as the ability to activate the device with 1 hand. [12][13][14] Instruction and training are likewise regulated.…”
mentioning
confidence: 99%
“…2,6,[15][16][17] These investigations repeatedly found that most injuries occur before or even during activation of the safety-engineered protection mechanism. 2,6,8,9,11 For winged blood collection needles, the impact of the safetyengineered protection mechanism on the reduction of injury rates in healthcare personnel has been demonstrated. 2,18,19 In a previous study, more than 90% of the winged steel needles involved in injuries had sharps injury prevention features, yet the sharps injury rate remained at approximately 2 per 1,000 full-time employee equivalents in the study period.…”
mentioning
confidence: 99%